Effect of Gross Domestic Product and Exchange Rate on Yam Export Promotion in Nigeria: 2000 – 2023 - P.O. Idisi; I.M. Maduekwe; B.A. Adeagbo; D.A. Agbonika; Z.I. Abdulsalaam; C.E. Amadi; G.E Okoh; O.O. Ogunlade; P.W. Samaila; C. Clement (European Scientific Journal, ESJ, 2026)
This study investigated the Effects of GDP and exchange rate on Yam export promotion in Nigeria from 2000 to 2023. The study employed time series data. The Ordinary Least Squares (OLS) and Autoregressive Distributed Lag methods were used for the estimation of the models. The variables are stationary at level. The result of the trend estimation shows positive and significant at (P>1%) for Exchange Rate. The result of the trend estimation shows negative and significant at (P>1%) for Gross Domestic Product. The result of the trend estimation shows positive but not significant for Yam Export. The estimated Ordinary Least Square result shows that the coefficient of Exchange Rate (EXR) is negative and not significant in explaining Yam Export. The result also shows that the coefficient of Gross Domestic Product (GDP) is positive but not significant in explaining Yam Export. The estimated Autoreggressive distributed lag result shows that the coefficient of GDP (-1) is positive and significant at (P>5%) in explaining yam export . The result further shows that the coefficient of Exchange Rate is positive and significant at (P>10%) in explaining yam export. The result shows that exchange rate granger causes gross domestic product i.e unidirectional relationship in explaining yam export competitiveness. The result shows that GDP and exchange rate does not have causal relationship with yam export which implies that yam export is not competitive in Nigeria. It is therefore recommended that investing in modern farming, supply chains, and storage; diversifying export markets to Asia and the Middle East; stabilizing exchange rates for price predictability; and promoting value-added products like yam flour and chips. These measures can enhance yam export earnings and strengthen Nigeria’s economy.